Management structure, goals and policies for collective bargaining - Leap, Terry 1948- (1995)
This article turns its attention to management, opening with the basic goals and strategies of the management. Differences between unionized and non-unionized firms are explored. The author describes strategies for balancing power between unions and management, and for creating cooperative efforts between union and management.